Una Faccia, Una Razza: Similarities, Differences, and Parallels in Adult Education Policy Development in Greece and Italy - Koulaouzides, George; Romano, Alessandra (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2022)
There is little evidence about the origin of the phrase una faccia, una razza (one face, one race). However, its use signifies numerous shared elements in the cultures of Italy and Greece. In both countries, adult education emerged within the critical paradigm whereas vocationalism is currently the leading force of adult education policy development. The purpose of this article is to discuss the paths of adult education policy evolution over the last 40 years in both countries. Acknowledging Europeanization, neoliberalism, and vocationalism as the forces of policy change, the article provides a detailed critical review, a synthesis, and a proposal about future steps in adult education policy.